Use of herbal drugs in pediatrics (Research, Society and Development, 2021)
Objective: To discuss the use of herbal medicine adopted as therapy in children seen in pediatric outpatient clinics. Methodology: Exploratory, descriptive and cross-sectional study with a quali-quantitative approach. The research took place at Policlínica Santa Maria, Policlínica Orcino Guedes and Polisaúde, both with pediatric care and located in the city of Cajazeira-PB. The study sample consisted of 324 parents/guardians of children assisted in the aforementioned clinics, with data collection carried out in August, September and October 2021, through a validated instrument on the health and use of medicinal plants in children by the families. For data analysis, the SPSS v.25 program was used, in addition to Pearson's inferential chi-square tests, in addition to the technique proposed by Bardin. Inclusion criteria were: parents/guardians of children aged 0-10 years seen at the clinics, in the period corresponding to the research and who completed the form, excluding those who did not fill out the questionnaire correctly and those who were unable to inform about the use of herbal medicines. Results: It was analyzed that the most used medicinal plants in the city of Cajazeiras were: chamomile (17.5%) followed by lemongrass (8.8%) and Boldo (8%). In addition, it was identified that 73.1% of respondents use or have used medicinal plants for the prevention, cure or treatment of diseases in their children, of which 90.29% received guidance from their own family members. 219 respondents reported using the plants as teas. Conclusion: Having said that, it was observed that the use of medicinal plants is strongly present among parents in the city of Cajazeiras-PB.